All cause and cause specific mortality in 15-24-year-olds in Denmark 2010 to 2022: nationwide study of socioeconomic predictors - Janne S Tolstrup; Sofie Kruckow (BMJ Medicine)
Objective To assess inequalities in all cause and cause specific mortality in young people and if there are differences across gender and age groups.Design Nationwide cohort study of socioeconomic predictors.Setting Denmark, 1 January 2010 to 31 December 2022Participants All Danes of ages 15 to 24 years during the study period summing to a total of 9 314 807 person years and 2297 deaths. Participant and parental information were linked to obtain information on socioeconomic background to investigate differences in parents' educational level, employment status, and family's disposable income, using annually updated nationwide registers.Main outcome measures All cause and cause specific mortality including natural deaths (ie, medical conditions and diseases) and unnatural deaths (accidents, suicides, and homicides). Poisson regression was used to calculate incidence rate ratios and 95% confidence intervals (CI).Results Overall mortality rate was 24.7 (95% CI 23.7 to 25.7) and higher for men (33.2 (31.5 to 34.8)) compared with women (15.8 (14.6 to 16.9)). All cause and cause specific mortality were higher in financially disadvantaged groups compared with more affluent groups, and consistently so for all three measures of socioeconomic position. Results generally reflected a dose dependent association showing a higher mortality with lower levels of socioeconomic position. For instance, incidence rate ratios of all cause mortality related to parents' education was 2.3 (95% CI 2.0 to 2.7) for elementary level, 1.5 (1.3 to 1.6) for low, and 1.3 (1.1 to 1.4) for medium level as compared with high level. For deaths, incidence rate ratios of elementary education level compared with the most well educated group were 2.2 (1.5 to 3.2) for natural causes, 3.3 (2.5 to 4.4) for accidents, 1.6 (1.2 to 2.2) for suicides, and 3.1 (0.8 to 12) for homicides. Associations were similar in strata of men and women and by age group (15-17 v 18-24 years). Mortality in young men was considerably higher than in young women for all of the causes.Conclusion Young people from disadvantaged backgrounds have a markedly higher mortality from all causes than those from more affluent families. The socioeconomic position of their parents was associated with premature mortality in a dose dependent manner meaning that this effect is not only a concern for marginalised groups. Public health attention should be directed to respond to these inequities by strengthening advocacy for adolescent health, ensuring focus on adolescents in health policies and strategies, using the response to adolescent health as an indicator of equity, and prioritising research into the underlying mechanisms linking socioeconomic position in adolescence and mortality.